ESTERIFIKASI GLISEROL DAN ASAM LEMAK JENUH SAWIT DENGAN KATALIS MESA - Sri Wahyuni, Erliza Hambali, dan Bonar Tua Halomoan Marbun (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Glycerol esterification is one of methods that is widely used in the conversion of glycerol to producemore value-added products. The resulting products are environmentally friendly and renewable, so it couldpotentially be used by many industries. This study aimed to get the effects of various palm fatty acids and timeperiod of glycerol esterification reaction on physico-chemical properties of the resulting glycerol ester.Experiments used glycerol 94%, stearic acid, palmitic acid, myristic acid, and catalyst MESA 0.5%.Esterification process was performed at a temperature of 180°C, with a stirring speed of 400 rpm for 90 minutes,120 minutes and 150 minutes and supplied with nitrogen 100 cc/minutes. Physical and chemical properties ofglycerol ester resulted were influenced by the type of glycerol esters of fatty acids and process period ofesterification of glycerol ester produced. Yield, acid number, density, kinematic viscosity, flash point and pourpoint of glycerol ester of stearic, palmitic glycerol esters and glycerol esters of myristic showed ignificantlydifferent values. While the period of variation esterification process only affected the values of the yield and acidnumber. Physical and chemical properties of the three glycerol esters were produced yields of 96.1% (stearicacid), 95.86% (palmitic acid), and 95.99% (miristic acid); acid number of 24.84 mg KOH/g sample (stearicacid), 21.46 mg KOH/g sample (palmitic acid), 20.89 mg KOH/g sample (miristic acid); density of 0.903 g/cm3(stearic acid), 0.910 g/cm3 (palmitic acid), and 0.812 g/cm3 (miristic acid); kinematic viscosity (100°C)of 11.18cSt (stearic acid), 11.30 cSt (palmitic acid), and 4.26 cSt (miristic acid); flash point of 207oC (stearic acid),204oC (palmitic acid), and 173oC (miristic acid); and pour point of 55.5oC (stearic acid), 54oC (palmitic acid),and 57oC (miristic acid).Keywords: glycerol, fatty acid, MESA, esterification, glycerol ester